2012
DOI: 10.1007/s10096-012-1700-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of new automated cytomegalovirus IgM and IgG assays for the Elecsys® analyser platform

Abstract: Cytomegalovirus (CMV) is a leading cause of physical and neurological abnormalities in newborns. Hence, the diagnosis of CMV infection in pregnant women is necessary in order to allow appropriate management of their pregnancy. New assays have been developed for the Roche Elecsys® immunoassay platform that detect CMV-specific immunoglobulin (Ig)M and IgG, with the IgM assay designed to target IgM produced at the start of infection rather than IgM persisting later in infection. This study aimed to evaluate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…However, the identification of antibody types may help to determine the course of disease, and BIE may be used as a clinical primary screening tool for CMV patients. IgM is produced in large amounts early in infection (reaching a peak in the first month), and is followed by IgG production [ 7 , 31 ]. Levels of IgM decline in the months following the onset of infection, whereas IgG levels persist for the rest of the patient’s life [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the identification of antibody types may help to determine the course of disease, and BIE may be used as a clinical primary screening tool for CMV patients. IgM is produced in large amounts early in infection (reaching a peak in the first month), and is followed by IgG production [ 7 , 31 ]. Levels of IgM decline in the months following the onset of infection, whereas IgG levels persist for the rest of the patient’s life [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the CMV immunoglobulin G (IgG) avidity assay can help to distinguish primary from non-primary human CMV infections [ 3 5 ]. The key immune methods used for CMV antibody detection are: enzyme-linked immunosorbent assay (ELISA) [ 6 ], Elecsys [ 7 ], electrochemiluminescence immunoassay (ECLIA) [ 8 ], immunofluorescence assay (IFA) [ 9 ], flow cytometry (FCM) [ 10 ] and immunoblots [ 11 ]. Additionally, new immune methods for CMV antibody detection have been developed, such as the chemiluminesent microparticle immunoassay (CMIA) [ 12 ] and protein microarrays [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…IgM and IgG avidity assays available on new high throughput automated platforms have high sensitivity to diagnose primary infection. [7][8][9]16 Albeit some remaining pitfalls such as the interpretation of virological profile in serum with a low level of IgG, the tools available for the diagnosis of maternal primary infection are reliable. 10,11 The evaluation of the 4 most used CMV IgM assays in Europe reported that the mean sensitivity to diagnose a primary infection in the first trimester of pregnancy was 93.5% (range, 79.4%−98.0%).…”
Section: Yves Ville MDmentioning
confidence: 99%
“…• We propose an algorithm for the management of CMV primary infection in pregnancy. [19][20][21][22] Albeit some remaining pitfalls such as the interpretation of virological profile in serum with low level of IgG, the tools available for the diagnosis of maternal primary infection are reliable. 23,24 Maternal non-primary infection cannot be diagnosed by serology 25,26 and there are no other validated markers to identify seropositive pregnant women at risk of fetal transmission.…”
Section: T a B L Ementioning
confidence: 99%
“…IgM and IgG avidity assays available on new high throughput automated platforms have high sensitivity to diagnose primary infection 19‐22 . Albeit some remaining pitfalls such as the interpretation of virological profile in serum with low level of IgG, the tools available for the diagnosis of maternal primary infection are reliable 23,24 …”
Section: Prevention Of CMV Transplacental Transmission From Mother To Fetusmentioning
confidence: 99%